Cerebellar Development and Autism Spectrum Disorder in Tuberous Sclerosis Complex. (December 2015) - Sundberg, Maria; Sahin, Mustafa
Approximately 50% of patients with the genetic disease tuberous sclerosis complex present with autism spectrum disorder. Although a number of studies have investigated the link between autism and tuberous sclerosis complex, the etiology of autism spectrum disorder in these patients remains unclear. Abnormal cerebellar function during critical phases of development could disrupt functional processes in the brain, leading to development of autistic features. Accordingly, the authors review the potential role of cerebellar dysfunction in the pathogenesis of autism spectrum disorder in tuberous sclerosis complex. The authors also introduce conditional knockout mouse models of Tsc1 and Tsc2 that link cerebellar circuitry to the development of autistic-like features. Taken together, these preclinical and clinical investigations indicate the cerebellum has a profound regulatory role during development of social communication and repetitive behaviors.